All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 58862 by George Mark Samuel last updated on 01/May/19
2x+y=6y3x=3(2y−1)solveforxandy
Answered by MJS last updated on 01/May/19
2x+y=6y2x×2y=2y×3y2x=3yxln2=yln3y=ln2ln3x3x=3(2y−1)3x−1=2y−1(x−1)ln3=(y−1)ln2xln3−ln3=yln2−ln2y=ln3ln2x−ln3ln2+1ln2ln3x=ln3ln2x−ln3ln2+1ln3ln2=axa=ax−a+1x=a2x−a2+ax(1−a2)=a−a2x(1−a)(1+a)=a(1−a)x=aa+1=ln3ln6y=1ax=1a+1=ln2ln6
Terms of Service
Privacy Policy
Contact: info@tinkutara.com